Quality Circles in Hospital: An Exploratory Study (Medico Legal Update, 2021)
Introduction: Quality circle (QC) consists of people working in a common work area, coming togethervoluntarily to identify, analyze and solve various quality related problems within their area.Methodology: The exploratory study was done in a hospital in India that was part of large public sectororganisation that ran the program of QC across its institutions and also in its non-core areas like the hospitals.Primary data was collected from the staff working in the hospital that was part of quality circles.Results: Most of the QC members reported an improvement in terms of the Job satisfaction andaccomplishment that was measured on the 6 parameters. The perception of the Non-members about thegeneral organizational climate was on the lower side in comparison to the members ofthe QCs. The membersof the QC seemed to fare better than the Non- members.Discussion and Conclusion: If the top and middle management develop faith and conviction in the efficacyof the QC program, then rolling this out is not an issue at all. Most of the members were appreciative of thefact that program of this kind was great learning experience. There was a unanimous agreement on the factthat this activity should continue and be extended to the whole of the organization in the whole country.The findings suggested that the employees saw positive changes after becoming part of QCs in regard totheir personal growth and they also perceived positive changes in certain important organizational aspectswhich helped them to function effectively.The organizational climate seemed to have improved with QC as reflected in job satisfaction and sense ofaccomplishment between QC members and non-Members.